2020
DOI: 10.1002/kjm2.12310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐181a attenuates sepsis‐induced inflammation and apoptosis by activating Nrf2 and inhibiting NF‐κB pathways via targeting SIRT1

Abstract: Sepsis is caused by microbial infection with high mortality worldwide, and characterized by multiple organ dysfunction and systemic inflammatory response. Previous study shows that miR‐181a level is increased during sepsis; however, the mechanism is still unknown. Therefore, to identify the role of miR‐181a, lipopolysaccharide (LPS) was used to stimulate mouse peritoneal macrophages. The expressions of miR‐181a and SIRT1 were identified by QRT‐PCR, the levels of SIRT1, Nrf2, p‐P65, Bcl‐2 and Bax were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…SIRT1 is a well-known regulator of chronic inflammatory responses, which has been investigated in the context of the alleviation of asthma as well as allergic rhinitis ( 15 , 59 ). Wu et al ( 60 ) found that SIRT1 activation upregulated Nrf2 expression and inhibited the NF-κB signaling pathway to relieve sepsis-induced inflammation and apoptosis. Furthermore, it was demonstrated in a previous study that formononetin served as a SIRT1 activator and improved diabetic neuropathy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a well-known regulator of chronic inflammatory responses, which has been investigated in the context of the alleviation of asthma as well as allergic rhinitis ( 15 , 59 ). Wu et al ( 60 ) found that SIRT1 activation upregulated Nrf2 expression and inhibited the NF-κB signaling pathway to relieve sepsis-induced inflammation and apoptosis. Furthermore, it was demonstrated in a previous study that formononetin served as a SIRT1 activator and improved diabetic neuropathy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs have critical impacts on the regulation of gene expression and associated biological processes such as proliferation, apoptosis, tumorigenesis [ 92 ], and even cell-cell communication (as suggested via vesicle-free extracellular miRNAs) [ 93 ]. Considering this regulatory role of miRNAs, and other transcription regulatory molecules involved in the Nrf2 pathway (such as miR-365-1, miR-193b, miR-29-b1, miR-93, miR-153, miR-27-a, miR-142–5p [ 94 ], miR-21 [ 95 ], miR-144 [ 96 ], miR-125b [ 97 ], miR-181a [ 98 ], hsa_circ_0005915 [ 99 ], miR-145–5p, miR-104–5p, miR-200a [ 100 ]) may be important to evaluate CBD action which may have a great potential to change Nrf2 activity.…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...mentioning
confidence: 99%
“…35 Our results showed that SEV up-regulated IκBα expression and down-regulated the expressions of p-p65 and acetyl-p53 in LPS-induced HK-2 cells, indicating activating the NF-κB signaling pathway 46 and sepsis-induced inflammation and apoptosis could be alleviated by inhibiting the NF-κB pathway via targeting SIRT1. 47 Therefore, we speculated that SEV suppressed the apoptosis of LPSinduced HK-2 cells by promoting the SIRT1 expression and inactivating the NF-κB signaling pathway.…”
Section: Sev Inhibits the Activation Of Nf-κb Signaling Induced By Lp...mentioning
confidence: 99%